Using Sparkol Videoscribe as a Media for Learning Redox Reaction - Haetami, Aceng; Teewa, Sefrianty; Dahlan, Dahlan (FKIP Universitas Lampung, 2022)
This study determined the effectiveness of Sparkol video scribe media and students' responses to redox reaction learning. The sample in this study was 29 students of class X IPA2 SMA Negeri 1 Konawe Selatan, as many as 29 people. The research method used is a pre experimental research design One-group Pre-test Post-test Design. We collected data in this study using research instruments such as multiple choice questions, student and teacher activity observation sheets, and student response questionnaires to the learning process. The results showed that using sparkol video scribe learning media improved student learning outcomes from an average of 22.51 to 79.92 with effectiveness of 0.73 (high) and student responses of 70.69%. From the results of the analysis it was found that the use of sparkol videoscribe had an impact on the effectiveness of student learning and was able to have an impact on student involvement in learningKeywords: sparkol videoscribe, learning outcomes, redox reaction.DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp780-791